Adsorption of Acid Blue 129 from Aqueous Solutions onto Raw and Surfactant-Modified Bentonite: Application of Temperature-Dependent Forms of Adsorption Isotherms - Yesi; Fiona Patricia Sisnandy; Yi-Hsu Ju; Felycia Edi Soetaredjo; Suryadi Ismadji (Adsorption Science & Technology)
Modification of raw bentonite from Ponorogo, East Java, Indonesia by microwave irradiation using cetyltrimethylammonium bromide (CTAB) was studied. The adsorption capabilities of raw bentonite and its modified form were examined through their use in the removal of Acid Blue 129 from aqueous solution. The adsorption isotherm and kinetic experiments were conducted at four temperatures (25, 30, 40 and 50 °C). The fitting of the corresponding experimental data was tested using the temperature-dependent forms of the Langmuir, Freundlich, Sips and Toth equations. The Sips equation gave a better representation of the adsorption data, together with reasonable values of the fitted parameters. Two well-known kinetic models, the pseudo-first- and pseudo-second-order, were used to correlate the adsorption kinetic data, with the pseudo-first-order model giving the better results. Both physical and chemical adsorption mechanisms occurred during the adsorption process, with the main controlling mechanism being physical adsorption.